THE CALCINATION TEMPERATURE EFFECT ON THE ANTIOXIDANT AND RADIOPROTECTION PROPERTIES OF CeO2 NANOPARTICLES - Iis Nurhasanah; Weni Safitri; Tri Windarti; Agus Subagio (Dept. of Chemical Engineering, Diponegoro University, 2018)
The CeO2 nanoparticles are very interesting to be studied as biomedical materials due to its unique physical and chemical properties. The non-stoichiometric properties of CeO2 play a role in the redox/catalytic processes that scavenging free radicals. These properties make CeO2 nanoparticles as being potentially antioxidant and radioprotector materials. In this paper, we report the calcination temperature effect on the antioxidant properties and radioprotective effect of CeO2 nanoparticles synthesized by precipitation method. The CeO2 nanoparticles were synthesized by precipitation method at various calcinations temperatures (300oC – 700oC). The formation of CeO2 nanoparticles and crystallite size was analyzed using X-ray diffractometers. The DPPH method was used to investigate antioxidant properties of CeO2. Dose Enhancement Factor (DEF) of CeO2 nanoparticles were determined by measurement of the absorbed dose of X-ray radiation (Linac 6 MV 200 MU). X-ray diffraction pattern showed formation of cubic fluorite of CeO2 nanoparticles with crystallite size in the range 9 nm-18 nm. Calcination temperature of 500oC resulted in CeO2 nanoparticles with the best antioxidant properties and lowest DEF value. The radioprotection effect of CeO2 nanoparticles was evaluated based on Escherichia coli survival toward X-ray radiation with a dose of 2 Gy. The CeO2 nanoparticles increased Escherichia coli survival of about 24.8% order. These results suggested that CeO2 nanoparticles may potentially be as radioprotector of X-ray Linac 6 MV. Keywords: Antioxidant, CeO2 nanoparticles, Dose Enhancement Factor (DEF), radioprotector